Sacubitril/Valsartan Alleviates Experimental Autoimmune Myocarditis by Inhibiting Th17 Cell Differentiation Independently of the NLRP3 Inflammasome Pathway - Liang, Wei; Xie, Bai-Kang; Ding, Pei-Wu; Wang, Min; Yuan, Jing; Cheng, Xiang; Liao, Yu-Hua; Yu, Miao (Frontiers in Pharmacology, 2021)
Sacubitril/valsartan (Sac/Val) is a recently approved drug that is commonly used for treatment of heart failure. Several studies indicated that Sac/Val also regulated the secretion of inflammatory factors. However, the effect and mechanism of this drug modulation of inflammatory immune responses are uncertain. In this study, an experimental autoimmune myocarditis (EAM) mouse model was established by injection of α-myosin-heavy chain peptides. The effect of oral Sac/Val on EAM was evaluated by histological staining of heart tissues, measurements of cardiac troponin T and inflammatory markers (IL-6 and hsCRP). The effects of Sac/Val on NLRP3 inflammasome activation and Th1/Th17 cell differentiation were also determined. To further explore the signaling pathways, the expressions of cardiac soluble guanylyl cyclase (sGC) and NF-κB p65 were investigated. The results showed that Sac/Val downregulated the inflammatory response and attenuated the severity of EAM, but did not influence NLRP3 inflammasomes activation. Moreover, Sac/Val treatment inhibited cardiac Th17 cell differentiation, and this might be associated with sGC/NF-κB p65 signaling pathway. These findings indicate the potential use of Sac/Val for treatment of myocarditis.